Synthetic Nucleosomes Reveal that GlcNAcylation Modulates Direct Interaction with the FACT Complex. (8th June 2016) - Raj, Ritu; Lercher, Lukas; Mohammed, Shabaz; Davis, Benjamin G.
Abstract: Transcriptional regulation can be established by various post‐translational modifications (PTMs) on histone proteins in the nucleosome and by nucleobase modifications on chromosomal DNA. Functional consequences of histone O‐GlcNAcylation (O‐GlcNAc=O‐linked β‐N‐acetylglucosamine) are largely unexplored. Herein, we generate homogeneously GlcNAcylated histones and nucleosomes by chemical post‐translational modification. Mass‐spectrometry‐based quantitative interaction proteomics reveals a direct interaction between GlcNAcylated nucleosomes and the "facilitates chromatin transcription" (FACT) complex. Preferential binding of FACT to GlcNAcylated nucleosomes may point towards O‐GlcNAcylation as one of the triggers for FACT‐driven transcriptional control.